Spain : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
Spain has achieved impressive growth in recent years-reflecting favorable competitiveness, and the impact on interest rates and confidence of its successful road to monetary union. Despite several years of rapid growth, there are no unambiguous signs of overheating. Underlying inflation has varied within a range of 2 percent and 2.5 percent on a 12-month basis since January 1997, but has exceeded the euro area average. Three years of steeply falling unemployment have yet to trigger a material acceleration of labor costs.